The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/hr.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

HSD11B2 CA-repeat and sodium balance

Abstract: Type 2 11β-hydroxysteroid dehydrogenase encoded by the HSD11B2 gene converts cortisol to inactive cortisone and thus protects the mineralocorticoid receptor from cortisol exposure. Impaired activity of this enzyme leads to mineralocorticoid excess, suggesting HSD11B2 as a candidate locus for patients at risk of developing low renin or salt-sensitive essential hypertension. In the present study, we searched for frequent polymorphisms in 155 Japanese subjects but detected none in the proximal promoter or coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies in humans suggest that 11βHSD2 in the brain may contribute to abnormal sodium homeostasis: increased salt appetite has been reported in AME 15 and loss-of-function variants positively associate with sodium intake in the general population. 16 Moreover, the sympathetic nervous system is activated in Hsd11b2 null mice, contributing importantly to the maintenance of hypertension in these animals. 11…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans suggest that 11βHSD2 in the brain may contribute to abnormal sodium homeostasis: increased salt appetite has been reported in AME 15 and loss-of-function variants positively associate with sodium intake in the general population. 16 Moreover, the sympathetic nervous system is activated in Hsd11b2 null mice, contributing importantly to the maintenance of hypertension in these animals. 11…”
Section: Introductionmentioning
confidence: 99%
“…In a large Japanese study, there was no significant difference in the distribution of the allele length between normotensive and hypertensive patients, or associations with urinary steroid ratios, but longer CA-repeat length was positively correlated with 24-h urinary sodium excretion. The authors suggested that HSD11B2 CA-repeat genotype was not associated with hypertension itself, but with renal sodium excretion, possibly by regulating salt intake/appetite [72]. Taken together, the results are tantalizing but inconclusive with regard to the effect of CA repeat length on the in vivo expression of 11-HSD2.…”
Section: Functional Roles Of 11-hsd2mentioning
confidence: 51%
“…The effects are reversed by MR antagonism or suppression of endogenous corticosterone [69]. Intriguingly, a longer HSD11B2 intronic CA repeat linked to modestly reduced enzyme activity associates with higher salt intake without changes in renal glucocorticoid metabolism [70], implying brain 11β‐HSD2 influences salt appetite in humans. There is an opportunity for elegant human experimental medicine studies.…”
Section: β‐Hsds In the Brain (Fig 2)mentioning
confidence: 99%